Dynamic changes of otolith organ function before and after repositioning in patients with benign paroxysmal positional vertigo detected by virtual reality auxiliary technology: A cohort study - Zhao, Chunjie; Yang, Qingjun; Song, Jijun (Frontiers in Neurology, 2022)
Objectives: To dynamically investigate otolith function in patients with benign paroxysmal positional vertigo (BPPV) before, after, and 1 month after repositioning, and explore the possible compensation mechanisms. Methods: Thirty-six patients confirmed with BPPV (canalolithiasis) treated in our hospital between August 2020 and March 2021, as well as 36 health controls matched for age and gender (normal control group, NC group) were enrolled. For NC group, the VR auxiliary static subjective visual vertical (SVV), subjective visual horizontal (SVH), and SVV of dynamic unilateral centrifugation (DUC), were measured at inclusion. For the BPPV group, visual analogue scale (VAS) was used to assess the vertigo degree, while static SVV,SVH, and DUC were performed before, after, and 1 month after repositioning. First, we compared the deviations of SVV0, SVH0, and SVV of DUC between BPPV and NC groups before repositioning, after which we compared the deviations in SVV45, SVV90, SVH45, SVH90, and SVV of DUC between the affected and unaffected sides before repositioning. Finally, paired t-test was used to compare the VAS score, deviations in static SVV0, SVV45, SVV90, SVH0, SVH45, and SVH90, and deviations in SVV of DUC before, after, and 1 month after repositioning. Results: SVV0, SVH0, and SVV of DUC at 120°/s 0 and 180°/s 0 significantly differed between BPPV and NC group before repositioning. The deviations in SVV45, SVV90, SVH45, SVH90, and SVV of DUC at 120°/s-2 and 180°/s-4.5 did not significantly differ between bilateral sides in BPPV patients before repositioning. The deviation in SVH90 was significantly lower after repositioning than before. The deviation in SVH45 was significantly higher 1 month after repositioning than before. The deviation angle of SVV of DUC at 180°/s-0 was significantly lower after repositioning than before. The vertigo degree continued to alleviate after repositioning. Conclusion: At disease onset, the function of otolith organs in BPPV patients was significantly decline, but the functions in bilateral ears did not significantly differ. The functions of otolith organs recovered immediately after repositioning, after which it gradually reduced, reaching similar levels to before repositioning.